Microenvironment Engineering for the Electrocatalytic CO2 Reduction Reaction - Lv, Jing‐Jing; Yin, Ruonan; Zhou, Limin; Li, Jun; Kikas, Reddu; Xu, Ting; Wang, Zheng‐Jun; Jin, Huile; Wang, Xin; Wang, Shun (Angewandte Chemie International Edition, 2022)
Rather than just focusing on the catalyst itself in the electrocatalytic CO2 reduction reaction (eCO2RR), as previously reviewed elsewhere, we herein extend the discussion to the special topic of the microenvironment around the electrocatalytic center and present a comprehensive overview of recent research progress. We categorize the microenvironment based on the components relevant to electrocatalytic active sites, i.e., the catalyst surface, substrate, co‐reactants, electrolyte, membrane, and reactor. Supported by most of the reported articles, the relevant factors affecting the catalytic performance of eCO2RR are then discussed in detail, and existing challenges and potential solutions are mentioned. Perspectives for the future research on eCO2RR, including the integration of different microenvironment factors, the extension to industrial application by coupling with carbon capture and conversion, and separation of products, are also discussed. This Review summarizes the impact of the microenvironment, including the catalyst surface, substrate, co‐reactants, electrolyte, membrane, and reactor, on the electrocatalytic CO2 reduction reaction (CO2RR). Different microenvironmental factors are discussed in the context of industrial applications, including coupling of CO2RR to carbon capture and conversion.